Effect of eccentric loading on energy absorbing circular cap and open end frusta tube structures. (August 2019) - Patel, Vivek; Tiwari, Gaurav; Dumpala, Ravikumar
Abstract: The response of cap end (C) and open end (O) frusta tube made of aluminium alloy AA-1080 were explored against eccentric loading by carrying out numerical simulation. The thickness of both type of frusta tube was varied as 1.15, 1.2 and 1.3 mm whereas height of open end and cap end frusta tube were considered as 91.6 and 103 mm respectively. The semi-apical angle was varied as 5.71°and 7.59° which resulted base diameter 60.8 and 67.2 mm for both type of tubes respectively. The variation in eccentricity of loading from the axis of the tubes was kept as 5, 8 and 12 mm. The numerical simulations were carried out by using commercial finite element code LS-DYNA. The performance of structures was decided based on crashworthiness parameters like Peak force, Mean crushing force, Crash load efficiency and Energy absorption capability. For validating the numerical results, experiments were performed on compression testing machine wherein both cap end and open end specimens with the thickness of 1.15 mm were compressed with eccentricity 5 mm. The actual results were found close enough with predicted results. Cap end structure showed higher Crash load efficiency and energy absorption compared to the open end frusta tube. Highlights: Functionally graded Cap end and Open end circular frusta tube structure were analysed under eccentric loading. Numerical results were validated with the experimental results. Validated numerical model used for further simulation. Thickness, taper angle and eccentricity were considered as important parameter that reflect it crashworthiness performance. Energy absorption capacity was more for cap end frusta tube.